Perfil clínico-epidemiológico de pacientes submetidos à cirurgia bariátrica - Araújo, Gabriella Bisi; Brito, Ana Paula Santos Oliveira; Mainardi, Carolina Ribeiro; Martins Neto, Eduardo dos Santos; Centeno, Deborah Marques; Brito, Marcus Vinicius Henriques (Pará Research Medical Journal, 2017)
Purpopse: This study aimed to verify, through review of 200 medical charts, the epidemiological factors of obese patients undergoing bariatric surgery, linked to a private clinic in Belém, Pará. Methods: It was performed the random review of 200 medical records. Were included in the survey: ages between 21 and 70; obese patients, or BMI greater than or equal to 40 kg/m2 with or without co-morbidities, or greater than or equal to 35Kg/m2 with comorbidities, who underwent bariatric surgery. Results: The results were an average age of 35 years (third decade of life - 41.5%), predominantly female (81%), white (70.5%), married (64%), graduated professionals (36%), sedentary (83%), alcoholism (58%), score BMI of 45.10 kg/m2 (morbid obesity - 65.5%), education level of third degree (91.5%) and, on the origins, the 200 patients (100%) were natural of the Pará state. Arterial hypertension was the most frequent comorbidity (68%), followed by arthropathies (46%), dyspnea on exertions (43.5%), diabetes mellitus (41.5%) and depression (35%). Conclusion: The profile of the operated patients was of women in the third decade of life, white, married, with complete university education, sedentary, alcohol consumers, morbidly obese and born at the state of Pará, being the most frequent comorbidity arterial hypertension.